Pemetaan Orientasi Visi Misi Perguruan Tinggi Swasta Di Wilayah Kopertis V Yogyakarta - Lucia Ika Fitriastuti (Jurnal Solusi, 2018)
The formulation of a right and realistic vision and mission in an organization plays an important role in achieving organizational goals. The vision and mission that has been determined will show the orientation of the organization. This study was interested to discussing how the orient the vision and mission at private universities in the Kopertis V area of Yogyakarta. The purpose of this study was to obtain an overview or mapping of vision and mission orientation at private universities in the Kopertis V region of Yogyakarta. The sample used is a total sample or the entire population. This study analyzed all private universities in the Kopertis V Yogyakarta area. The data source is the Kopertis V directory book. Analysis is done by content / content analysis, then using percentage calculations and data comparisons. The results show that the focus of the university’s vision and mission orientation is about the quality of graduates, both in terms of competence and ethics. Followed by the second order, private universities has begun to take into account their position towards other universities, so that in their vision and mission they declare their superiority at the national and global / international level. Third place, oriented to the interests of society and the State. The majority of private universities in Yogyakarta (91%) explained tridarma activities in their mission statement, the rest (9%) did not explain tridarma.